Раскопки городища Китея - Молев, Е.А. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the research of a Bosporan city Cytae. It resulted in the obtaining the additional arguments for the existing of a sacral complex on its territory from the beginning of the 4th c. BC to the 5th c. AD. The probability of localization of fosse in front of the northern line of fortifications was specified.